Radiographic follow‐up of pneumonia in children - Virkki, R. (Pediatr Pulmonol, 2005)
This study assessed the clinical value of routine follow‐up chest radiographs in hospitalized children with community‐acquired pneumonia. The study population consisted of 196 children hospitalized for community‐acquired pneumonia diagnosed between 1993–1995. Seventeen infective agents (10 viruses and 7 bacteria) were sought. Chest radiographs were taken on admission and 3–7 weeks later. All children were treated with antibiotics. Data on the course of illness over the following 8–10 years were obtained from patient files and questionnaires sent to parents. A potential causative agent was found in 165 (84%) of 196 cases. On follow‐up chest radiographs, residual or new changes were seen in 30% of cases. The residual changes tended to be more common after mixed viral‐bacterial infection (43%) than after sole viral (25%) or sole bacterial (20%) infection. Interstitial infiltrates (66%), atelectasis (46%), and enlarged lymph nodes were the most common sequelae seen on follow‐up. Residual findings on follow‐up radiographs did not affect the treatment of the children. No further chest radiographs were taken. During the 8–10‐year follow‐up of 194 children, no illnesses appeared that were associated with previous pneumonia. Twenty‐six children had a new episode of pneumonia, 7 of them had asthma, and 6 had different underlying illnesses. In conclusion, routine follow‐up chest radiographs are not needed in childhood community‐acquired pneumonia if the child has a clinically uneventful recovery. Pediatr Pulmonol. © 2005 Wiley‐Liss, Inc.